The Digital Literacy for Character Building: A Narrative Review on the Mediating Role of Elementary School Culture - La Ode Fajrul Islam Sabti (Institute Journal and Publication Muhammadiyah University of Buton, 2025)
Digital transformation creates a dual challenge for character education in elementary schools: harnessing the potential of technology while mitigating its risks. Digital literacy, initially instrumental, has now evolved into a socio-ethical competence (digital wisdom). However, its effectiveness in shaping character depends on the context of its implementation. This narrative review aims to analyze the role of school culture as a mediator in the relationship between digital literacy and students’ character formation. A review of 10 articles (2016–2025) reveals that school culture functions as an active mediating space, not merely a passive context. Four key mediating mechanisms are identified: (1) norms and habituation, (2) tripartite collaboration, (3) structured policies, and (4) socio-emotional learning (SEL) climate. School culture acts as a selective filter and amplifier, determining the direction of digital literacy’s dual impact. In conclusion, the success of integrating digital literacy for character is largely determined by the quality of school culture as a transformative medium that connects technical competence with the internalization of values.